2000
DOI: 10.4049/jimmunol.164.11.5771
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting Tolerance Induced by Autoantigen in Incomplete Freund’s Adjuvant

Abstract: Injection of autoantigens in IFA has been one of the most effective ways of preventing experimental, T cell-mediated, autoimmune disease in mice. The mechanism that underlies this protection has, however, remained controversial, with clonal deletion, induction of suppressor cells or of type 2 immunity being implicated at one time or another. Using high resolution enzyme-linked immunospot (ELISPOT) analysis, we have revisited this paradigm. As models of autoimmunity against sequestered and readily accessible au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
55
2

Year Published

2002
2002
2009
2009

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 77 publications
(65 citation statements)
references
References 75 publications
8
55
2
Order By: Relevance
“…IL-5 producers, which are prevalent after a single i.p. Ag:IFA injection (21,22) and which also become prominent after repeated s.c. injections (Fig. 2), were present in low but clearly detectable frequencies, at 27 per million spleen cells in primarily injected mice.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…IL-5 producers, which are prevalent after a single i.p. Ag:IFA injection (21,22) and which also become prominent after repeated s.c. injections (Fig. 2), were present in low but clearly detectable frequencies, at 27 per million spleen cells in primarily injected mice.…”
Section: Discussionmentioning
confidence: 98%
“…Ag injections with IFA are not a conceivable treatment for humans; however, s.c. injections with mineral oil (or with related lipids) are approved for clinical studies. Our previous studies have suggested that the protective effect of autoantigen:IFA injections in autoimmune models is Ag specific and T cell mediated: this treatment also protects B cell knock out mice, and the protection can be adoptively transferred with T cells (22). Unlike the immune-modulating effects of i.p.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations